A comparative analysis of the legal frameworks for SIA and EIA in Malaysia - M Suaree, Nur Atheefa Sufeena; Syed Abdul Kader, Sharifah Zubaidah; Mohamed Osman, Mariana; Abdul Manaf, Zati Ilham; Wan Jaffree, Wan Khubaib Akram (Malaysian Institute Of Planners, 2023)
Environmental Impact Assessment (EIA) and Social Impact Assessment (SIA) are the primary assessment tools used to generate information on the likely impacts of a project on all aspects of the environment and society, aiding the decision-making process to achieve sustainable development. While EIA is mainly concerned with assessing the potential environmental consequences of a proposed development, SIA evaluates the potential social consequences. These two mechanisms play a crucial role in promoting resilient and sustainable development in Malaysia. The legal framework for EIA has been enforced since 1988 and evolved through several legislations, including the Environmental Quality (Amendment) Act 2012 (Act A1441), very much earlier compared to the SIA legal framework, which was introduced in 2017 by virtue of the Town and Country Planning (Amendment) Act 2017(Act A1522). Thus, this paper aims to analyse the legal framework of both assessment mechanisms, employing the qualitative method of library research, content and comparative analysis. The result shows that the EIA framework is more comprehensive and practical and is an effective model for the improvement of the SIA framework in Malaysia.